2022
DOI: 10.3390/brainsci12060743
|View full text |Cite
|
Sign up to set email alerts
|

Defining Expressive Language Benchmarks for Children with Down Syndrome

Abstract: Establishing expressive language benchmarks (ELBs) for children with Down syndrome (DS), as developed by Tager-Flusberg et al. for children with autism, is critically needed to inform the development of novel treatments, identify individualized treatment targets, and promote accurate monitoring of progress. In the present study, we assessed ELB assignments in three language domains (phonology, vocabulary, and grammar) for 53 young children with DS (CA range: 2.50–7.99 years) using standardized assessments. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…12 A recent meta-analysis of predictors of language outcomes for children with DS across 170 children in 9 separate studies revealed that adaptive functioning, vocabulary, maternal education, communicative intent, phonological awareness, parental translation of gesture, baby sign, nonverbal mental ability, and joint attention were predictive of later language, although this study did not include other patient-specific health or environmental characteristics. 13 In a recent study by Thurman et al, 14 it was demonstrated that children with DS do have significant variability in expressive language benchmarks by age, although that study was limited to children between the ages of 2.50 and 7.99 years. There are hypotheses regarding the drivers of poor expressive language outcomes, but these have not been evaluated in a large sample to examine potential variables of impact across a cohort of children and young adults with DS.…”
mentioning
confidence: 99%
“…12 A recent meta-analysis of predictors of language outcomes for children with DS across 170 children in 9 separate studies revealed that adaptive functioning, vocabulary, maternal education, communicative intent, phonological awareness, parental translation of gesture, baby sign, nonverbal mental ability, and joint attention were predictive of later language, although this study did not include other patient-specific health or environmental characteristics. 13 In a recent study by Thurman et al, 14 it was demonstrated that children with DS do have significant variability in expressive language benchmarks by age, although that study was limited to children between the ages of 2.50 and 7.99 years. There are hypotheses regarding the drivers of poor expressive language outcomes, but these have not been evaluated in a large sample to examine potential variables of impact across a cohort of children and young adults with DS.…”
mentioning
confidence: 99%